Women’s Perceptions Using the CenteringPregnancy Model of Group Prenatal Care - Risisky, Deb (Springer Publishing Company, 2013)
A qualitative nonexperimental thematic analysis was conducted at a hospital-based midwifery practice to explore the views of participants in group prenatal care and its impact on pregnancy, birth, and postnatal care. Ten women and three support people, recruited through purposive sampling, shared their feedback on the program. The findings conveyed three broad themes: program experience, midwife relationship, and support. Women enjoyed the opportunity for in-depth learning, and peer-group support led to normalizing of pregnancy concerns. Having support people as participants also helped during pregnancy, birth, and child care. The findings showed the enhanced opportunity for education, learning, and interpersonal support provided by CenteringPregnancy to expectant mothers had a positive impact on their pregnancy experiences.